Determinan Keterlambatan Audit pada Perusahaan di Pusat Pasar Modal: Bukti dari Sektor Properti dan Real Estat - Adila Saputra; Jejen Jaenudin (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2026)
Essentiality of prompt audited financial reporting for transparency and investor confidence in capital market facilities in developing countries is the basis for this research. Although financial compliance requirement reports must be delivered within the specified timeframe, audit delays still occur frequently, especially in the property and real estate firms,that are characterized by complexity and high risk. The key aspect of this paper is to assess of audit delay, including company complexity, the entity's ability to settle its liabilities, and the efficacy of the audit committee. Publicly listed property and real estate firms in Indonesia website from 2018–2023 were used utilized as research data and examined using a panel data regression approach. The results attest that solvency has yields positive results on audit delay, proving that high solvency requires longer audit time for auditors. Meanwhile, company complexity and the audit committee not account for the variance on audit delay. Simultaneously, the three variables were unable to significant clarify the inconsistency audit delay. Those finding implies the financial risk factors remain the primary determinant of audit delays in the submission of audit reports for property and real estate entities in capital market centers.